2012
DOI: 10.1007/s11229-012-0182-z
|View full text |Cite
|
Sign up to set email alerts
|

Combining psychological models with machine learning to better predict people’s decisions

Abstract: Creating agents that proficiently interact with people is critical for many applications. Towards creating these agents, models are needed that effectively predict people's decisions in a variety of problems. To date, two approaches have been suggested to generally describe people's decision behavior. One approach creates a-priori predictions about people's behavior, either based on theoretical rational behavior or based on psychological models, including bounded rationality. A second type of approach focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…While the accurate prediction of an insider's moves was the main motivation, only Nash equilibrium analysis has been used to capture the insider's future actions, in order to respond properly. It is well known that people do not follow Nash equilibrium strategies [77], [78] including intelligent security people [79]. In addition, the game is a one-shot game, and a discussion on repeated games was not included.…”
Section: F Game Theory Approachesmentioning
confidence: 99%
“…While the accurate prediction of an insider's moves was the main motivation, only Nash equilibrium analysis has been used to capture the insider's future actions, in order to respond properly. It is well known that people do not follow Nash equilibrium strategies [77], [78] including intelligent security people [79]. In addition, the game is a one-shot game, and a discussion on repeated games was not included.…”
Section: F Game Theory Approachesmentioning
confidence: 99%
“…It has already been suggested that achieving successful human–machine collaboration requires the modeling of human behavior for predicting people’s decisions [ 7 , 8 ]. It has been shown, for example, that information about drivers (i.e., driving style) improves the prediction models regarding the use of an automated assistive system [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We expect that this general approach will apply well to dealing with humans despite the wide range of behaviors that humans can exhibit. This expectation is supported by research showing that a small number of behaviors captures the majority of human behaviors in certain tasks [108]. Similarly, research on bandit problems suggests that only a limited number of strategies are viable in social settings [97].…”
Section: Human Interactionsmentioning
confidence: 89%
“…This case is of interest because a finite set of behaviors can often cover the space of likely behaviors. For example, analysis of bandit problems [97], ad hoc teamwork [19], and using machine learning with psychological models [108] suggests that a small number of behaviors can represent the spread of possible behaviors.…”
Section: Teammates From a Finite Setmentioning
confidence: 99%